Caracterização dos produtores familiares e da produção de leite em Capitão Enéas / Minas Gerais, 2000. - Leocadia de Fatima Vieira Zuba (2001)
The following work has as its main objective to delineate the milk production and to identify the cooperative action in a associative unit in a Farming and Cattle Raising Region Cooperative members in Montes Claros. municipal district of Capitão Enéas. in Minas Gerais. In a 100 group. 30 milk producers were randomly selected and economic outline of the producer. the country estate on itself, its natural and tecnological resourcers and the zoo-sanitary cares. The milk production was investigated on its milking, storage and transportation, granalization. coopoerative action, technical, financial and accouting assistence. The results showed the producers are all men.and over 41.5 years old and they haven't completed the elementary school (80%). They all have lived there for more than lived there for more than 20 years and the country estates were acquired from heredity, keeping them as they were in the past. The country estates had different size: little ones (from 35 to 130 hc), medium ones (from 150 to 495 hc) and the biggest ones (more than 500 hc). Five people or more lived in 53% of the properties and 47% or less lived in them. In all the country estates de production was centered on the head os the family behalf, even its administration and the work execution. The low income milk prodution was the matter of fact, showing a little exploration of resources. 80% from the interviewed producers had as its main milk activity problem the capital lack to finance the production, the storage and milk trandportation besides the low price paid for the product. It was noticed the lack of technical knowledge and systematic control from the producers, cattle commanding, milking, storage, transportationand book-keeping. These bars for little and intermediate producers to progress even some medium ones to join the granalization process offer. The little and intermediate producers even some medium ones are supposed to be excluded if they don't try immediate actions to develop the milk production and its quality.